Hypoglycemia evaluation and reporting in diabetes: Importance for the development of new therapies. Issue 5 (7th March 2017) - Klonoff, David C.; Alexander Fleming, G.; Muchmore, Douglas B.; Frier, Brian M.
Abstract: Hypoglycemia complicating diabetes therapy is well recognized to be an ever‐present threat to patients, their families, providers, payers, and regulators. Despite this being widely acknowledged, the regulatory stance on hypoglycemia as an endpoint in clinical trials to support new product registration has not evolved in any meaningful way since the publication of a position paper by an American Diabetes Association (ADA) Workgroup in 2005. As the impact of hypoglycemia on persons affected by diabetes is of major importance when assessing new treatments, the historical position of regulatory agencies on hypoglycemia is reviewed with respect to product approvals. The purpose of this article is to present proposals for facilitating development of therapies that reduce hypoglycemia risk through (1) development of composite measures of benefit for regulatory endpoints and (2) facilitation of the fulfillment of an unmet clinical need for reducing hypoglycemia. In view of greater comprehension of the effects of hypoglycemia, coupled with improved methodology to assess its frequency, the authors recommend: (1) a numerical cut point of <54 mg/dl (<3.0 mmol/L) as a clinically relevant level with which to define meaningful hypoglycemia for trials of diabetes therapies; (2) utilization in clinical trials of mature glucose monitoring technologies for purposes of regulatory evaluation and clinical decision‐making; and (3) development of primary efficacy endpoint composites that include hypoglycemia rates and glycemic control.